Structural characterization, hydrolytic stability and dynamics of cis-MoVIO2 2+ hydroquinonate/phenolate complexes - Drouza, Chryssoula; Hadjithoma, Sofia; Nicolaou, Maria; Keramidas, Anastasios D. (My University, 2018)
Although, the investigation of the interactions of MoVI ion with the “non-innocent” phenols/hydroquinones is essential for the understanding of the role of molybdenum in the biological systems, the MoVI complexes of phenolate/hydroquinonate and their functionalized variants remain mainly unexplored. Reaction of Na2MoVIO4 with tripod iminodiacetate phenol/hydroquinone ligands in aqueous solutions resulted in the synthesis of mononuclear phenolate/hydroquinonate and dinuclear bridged-hydroquinonate cis-MoVIO22+ complexes. The new complexes were isolated and characterized in solid state by X-ray crystallography. The 1H, 13C and 95Mo NMR spectra of the aqueous solutions of the complexes show that they retain their structure at the pD range 2–4, with the dinuclear bridged-hydroquinonate cis-MoVIO22+ to form two isomers which are in dynamic equilibrium. At pDs 4–7 the MoVI-Ophenolate bond of the cis-MoVIO22+ compounds hydrolyzes to form MoVIO3-iminodiacetate species. Variable temperature (VT) and 2D {1H} EXSY NMR spectroscopies where employed for the determination of the thermodynamic and activation parameters of the isomerization reaction between the dinuclear bridged-hydroquinonate cis-MoVIO22+ isomers. The exchange mechanism between cis-MoVIO22+ and the MoVIO3 species were also investigated by 2D {1H} EXSY NMR spectroscopy. Despite of the higher strength of the MoVI-Ophenolate bond, it is more labile than the MoVI-Ocarboxylate bond. The rate determining step of the above exchange reactions was found to be the dissociation of the phenolate/hydroquinonate oxygen atom from MoVI ion.
Keywords: Hydrolytic stability; Hydroquinones; Kinetics; Molybdenum; Non-innocent ligands